The Encyclopedia Americana International Edition in Volume 29 - The Encyclopedia Americana (Americana Corporation, 1972)
The Encyclopedia Americana Provides special features that help the reader find and organize information for example,separate articles on each of the centuries A.D ( First Century " to" Twentieth Century " ) Cut across political boundaries to set history in international perspective